Technical efficiency of secondary health care service delivery in the Gambia - Jarjuea, Gibril; Mohamed Nor, Norashidah; Abdul Ghani, Judhiana; Abd Jalil, Suhaila (Faculty of Economics and Management, Universiti Putra Malaysia, 2015)
This study is conducted with specific objectives: a) To measure the technical and scale efficiency of the health centers in the Gambia; b) To estimate the amounts of output increases and/or input reductions that would be required to make inefficient health centers more efficient. The study uses output-oriented variable return to scale Data Envelopment Analysis (DEA) method. The findings show that 9 (22%) health centers are efficient, 32 (78%) health centers are technically inefficient with an average technical efficiency score of 65% and standard deviation (STD) of 26%. Furthermore, 4 (10%) health centers are scale efficient, 37 (90%) health centers scale inefficient with an average scale efficiency score of 87% and standard deviation (STD) of 12%.The widespread inefficiency across the entire secondary health care service delivery system in the Gambia is alarming and the results suggest that health centers are using resources more than they actually need.